Generation mean analysis of maydis leaf blight resistance in maize - M.C. KAMBOJ and R. MEHRA, PREETI SHARMA*, M.S. PUNIA (Indian Phytopathology, 2017)
Studies on inheritance of the disease resistance were conducted on ten crosses using six generations derived from 4 susceptible (HKI 209, HKI 1332 , HKI 488-1RG and HKI 325-17AN) and 4 resistant inbred lines (HKI 1128, HKI 163, HKI 164D-4-(O) and HKI 193-2-2). The genetic material for field evaluation comprised of six generations i.e. 5 parental inbred lines (P1 and P2), 6 F1’s, their F2 and back crosses (BC1 and BC2) of ten crosses were studied for reaction to maydis leaf blight at CCS, HAU Regional Research Station, Karnal, during Kharif 2014. Significant additive and dominance variances were observed in most of the crosses. The study suggested that both additive and dominance components were important in the inheritance of maydis leaf blight, the magnitude of additive component being relatively higher than non-additive component. Cross HKI 209 x HKI 193-2-2, HKI 488-1RG x HKI 164D-4-(O) and HKI 325-17AN x HKI 164D-4-(O) were found to have duplicate type of epistatis. Gene interactions and environment were also found to be important. The higher estimates of additive component of variance, heritability and genetic advance indicated that selection for maydis leaf blight resistance is likely to be more effective.